2020
DOI: 10.1177/0300060520924550
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and laboratory results of 61 children with infectious mononucleosis

Abstract: Objective To investigate the clinical manifestations of infectious mononucleosis in children of different ages. Methods Clinical data from pediatric patients with infectious mononucleosis admitted from May 2015 to April 2019 were retrospectively analyzed. Patients were stratified into three groups (age 1–3 years, 4–6 years, and 7–14 years) for analysis of clinical and laboratory results. Results Data from 61 patients (male:female ratio 1.18:1) aged 5.15 ± 2.93 years (mean ± standard deviation; range: 1–14 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…In IM children with simple EBV infection, the damage of liver function becomes more and more serious with the increase of age. At present, there are few reports about IM combined with other pathogen infections and grouped by age at home and abroad, and only literatures about IM grouped by age caused by EBV infection also found that ALT significantly increased in older children [20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…In IM children with simple EBV infection, the damage of liver function becomes more and more serious with the increase of age. At present, there are few reports about IM combined with other pathogen infections and grouped by age at home and abroad, and only literatures about IM grouped by age caused by EBV infection also found that ALT significantly increased in older children [20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…Infectious mononucleosis (IM) has a high incidence rate in children, which is often caused by the infection by the herpes family virus Epstein–Barr virus (EBV). The main clinical symptoms include angina, fever, hepatosplenomegaly, and so on [ 1 ]. If not treated in time, the disease easily develops into a malignant disease related to chronic active EBV infection and causes multisystem damage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…За даними Всесвітньої організації охорони здоров'я, захворюваність на герпетичну інфекцію у світі невпинно зростає й охоплює близько 96 % населення планети [1,5,7,10]. Найвищий рівень інфікованості виявлений серед дитячого населення, проте через субклінічний перебіг захворювання не завжди вдається його діагностувати на ранній стадії [2,3].…”
Section: вступunclassified
“…У групі 1 рівень загального білірубіну становив 20,1 [16,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]8] мкмоль/л і був вірогідно вищим від аналогічного показника дітей групи 2. Підвищення вмісту загального білірубіну відбувалося за рахунок прямого білірубіну, а рівень непрямого білірубіну в досліджуваних групах відрізнявся незначно і становив 11,9 [10,8-13,2] мкмоль/л у дітей групи 1 і 11,0 [10,[3][4][5][6][7][8][9][10][11]8] мкмоль/л -групи 2. Активність аланінамінотрансферази в дітей групи 1 становила 55,4 [37,2-3,7] Од/л і була вірогідно вищою порівняно з показниками в дітей групи 2 -33,3 [14,2-52,4] Од/л.…”
Section: результати та їх обговоренняunclassified